STRENGTHENING FINANCIAL LITERACY FOR INDONESIAN MIGRANT WORKERS IN MALAYSIA: "A STRATEGY TOWARDS FINANCIAL INDEPENDENCE” - Ali, Karnila; Dacholfany, Muhammad Ihsan; Fitriani, Fitriani; Darmayanti, Elmira Febri; Lelawati, Nina; Rolia, Eva (SINAR SANG SURYA, 2026)
Malaysia was the most frequently chosen country by Indonesian Migrant Workers (IMW) in 2024. Education on the importance of financial management for IMW is crucial. This is because the majority of IMW lack adequate knowledge of financial management. Observations through various media sources concluded that many IMW still lack adequate knowledge and understanding of financial literacy. This education is delivered through training aimed at teaching IMW the importance of financial planning. The materials provided include budgeting, saving, using digital financial applications and online banking services to facilitate transactions and money transfers, and investing, which are essential for effective personal financial management. Management Science University (MSU) Malaysia is a popular destination for Indonesians seeking further education and employment in the formal sector. According to MSU, approximately 200 Indonesian students are currently studying at MSU, with approximately 25 formal migrant workers employed on campus as lecturers and staff and informal workers around Shah Alam. This community service activity is an international collaboration between the Management Science University (MSU) Malaysia Lecturers and the Universitas Muhammadiyah Metro Lecturers. The community service activity takes the form of financial planning training, which is expected to equip Indonesian migrant workers (IMW) working around the MSU campus in Shah Alam with the knowledge necessary for proper financial management. Providing training and reinforcement regarding financial management and digital banking services will be effective in improving the financial literacy of formal and informal IMW working at MSU Malaysia campus and its surroundings.The implementation method for this training consists of four stages: planning, preparation, implementation, and evaluation. The short-term goal of this program is to successfully implement this community service activity, which is expected to serve as an alternative activity to strengthen the literacy of Indonesian migrant workers still working in MalaysiaKeywords: Training, Financial Literacy, Investment, Indonesian Migrant Workers